(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Progression of myopia in a pediatric or adolescent patient is asymmetric, with periods of rapid increase in axial (anteroposterior) length (and, consequently, in refraction) coinciding with periods of significant increase in anthropometric measurements. Previously, we have found an association between psychoemotional status and progression of disease, and developed psychological correction techniques for myopes. However, until now, there have been no data on the efficacy of the techniques developed for psychological correction of maladaptive impairments in the late period after treatment. Purpose: To assess the long-term results of psychological correction of maladaptive individual psychological features in patients with myopia. Materials and Methods: Seventy one myopic and 43 emmetropic students were placed under observation. We used the following tools to determine individual psychological features: the Spielberger State Anxiety Scale adapted by Khanin, the Differential Personality Questionnaire adapted by the Bekhterev Institute, the Ellis Irrational Beliefs System, the Amirkhan’s Coping Strategy Indicator, the Bekhterev Institute Personality Questionnaire and the Structured Clinical Diagnostic Interview. Assessment of psychoemotional status was performed under rest conditions and under academic examination stress conditions. Myopic students were divided into three groups based on the results of psychodiagnostic testing. Cognitive behavioral, rational emotive, art and pharmacological therapies were used to treat them. A year after completion of this treatment, they received psychodiagnostic re-testing and repeated therapy. Results: Following the use of complex medical and psychological corrective treatment, the amount of psychological impairments in myopic students was found to be statistically significantly reduced, whereas the rate of the use of active coping strategies aimed at an individual’s independent problem solving was found to be increased. This improvement maintained during one year of observation, with an increase in the number of patients with a realistic response to disease. However, one year after this treatment course, the numbers of patients with high situational anxiety, as well as with asthenic and affective manifestations of a psychopathological syndrome increased, requiring repeated psychological corrective therapy. Conclusions: The use of the proposed algorithm for psychological support of myopic patients enables effective correction of their psychoemotional status. The procedure is performed in stages, with stages 1 to 3 involving (a) psychoemotional status testing, (b) determination of targets of and formation of groups for psychological corrective therapy, and (c) differential use of cognitive behavioral and rational emotive therapies, respectively. The efficacy and duration of therapeutic effect of treatment performed were found to be improved with timely use of repeated psychotherapeutic courses.